The Clinical Observation of Acupuncture Combined With Antiemetic Drugs in the Prevention and Treatment of CINV in Breast Cancer Patients - Kong, Fanming; Wang, Ziwei; Wang, Na; Zhao, Lu; Mei, Qingyun; Yu, Yongchao; Zhang, Dou; Li, Xiaojiang; Jia, Yingjie (Frontiers in Oncology, 2022)
Objective The present study aimed to explore the effectiveness of acupuncture combined with antiemetic drugs in prevention and treatment of chemotherapy-induced nausea and vomiting (CINV) among breast cancer patients receiving postoperative adjuvant chemotherapy. Methods We retrospectively collected the clinical records of 81 postoperative breast cancer patients at our hospital from January 2021 to December 2021. These patients were divided into the acupuncture group and the control group. The efficacy of the antiemetic drugs combined with acupuncture for CINV was analysed. The primary endpoints were total, acute, and delayed nausea and vomiting grade and remission rate. Safety and overall patient quality of life were secondary endpoints. Results During the whole observation period, compared with the control group, the frequency of nausea and vomiting was decreased in the acupuncture group (P=0.034). And the ECOG-PS score in the acupuncture group was significantly improved (P=0.004). In addition, the adverse events, such as abdominal (12.2% vs. 5.0%, P=0.252), distention (19.5% vs. 5.0%, P=0.049), and diarrhea (9.7% vs. 0, P=0.044), were decreased by acupuncture. Conclusions Acupuncture combined with antiemetics could reduce the incidence of CINV, improve the quality of life of patients and reduce the incidence of adverse side effects of antiemetic drugs.